Occipital seizures imitating migraine aura. - Panayiotopoulos, C P (1997)
Three cases are reported in which symptoms of occipital seizures resembled the visual aura of migraine. Careful recording of the characteristics and timing of such visual effects will often resolve the diagnostic dilemma.